Peningkatan Aktivitas Belajar dan Hasil Belajar Matematika dengan Menggunakan Media Puzzle Pada Operasi Hitung Bilangan Kelas IV SDN 054932 Rantau Panjang - Novi Rahmawati; Hidayat Hidayat (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to increase the activity and results of learning mathematics by using puzzle media in arithmetic operations for class IV SDN 054932 Rantau Panjang. The design of this research is Classroom Action Research (CAR) model Mc. Kemmis and Taggart, namely research conducted for two cycles. The data collection instruments used were tests and observations. Data analysis techniques in this study used qualitative and quantitative data. Based on the results of the research, it is known that before being given class action the learning activities are unsatisfactory, the learning outcomes are not complete as much as 60% and the lack of use of learning media. So the researcher conducted a class action by using a puzzle media. The results of the optimal use of puzzle media are evident from the results of teacher observations in cycle I meeting one reaching 72% (good enough) increasing in meeting two reaching 78% (good), while for Cycle II meeting one reaching 74% (good enough) increasing in meeting two reached 80% (good), and in cycle III meeting one reached 94% (very good) increased at meeting two reached 98% (very good). For student activity in cycle I, meeting one reached 70% (good enough) increased at meeting two, reaching 76% (good), while in cycle II, meeting one reached 72% (good enough) and increased at meeting two to 86% (very good ). And in cycle III meeting one reached 92% (very good) increased at meeting two reached 98% (very good). Student learning outcomes in cycle I meeting one reached 45% (not good) increased at meeting two to 50% (poor), while in cycle II meeting one reached 72% (very good) increased in meeting two to 78% (very good ), and in cycle III the first meeting reached 81% (very good) increased at the second meeting to reach 90% (very good). Thus it can be concluded that using puzzle media in learning mathematics in arithmetic operations can increase activity and learning outcomes.